Cancer incidence among pharmaceutical workers - Edling, Chister; Friis, L.; Mikoczy, Zoli; Hagmar, Lars; Lindfors, Petra (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'A cluster of cancers at one plant in a pharmaceutical company in Sweden was the objective for this work, which describes the cancer incidence among the laboratory and production workers at this company.' ' METHODS ': 'The study is a retrospective cohort study. All employees with possible exposure to chemical, pharmacological or biological agents, and employment for at least six months at the company during 1960 -- 1990 were included. Standardized incidence ratios with the local county population as reference were calculated.' ' RESULTS ': 'The total cancer incidence was close to the expected. In a sub-cohort consisting of the highest exposed employees we found a SIR of 3.5 (95% CI = 1.5 -- 6.8) for urothelial tumors, while there were no urothelial tumors among the lowest exposed. An evaluation of the exposures among the subjects with urothelial tumors revealed no associations to specific exposures in the workplaces. There was also a statistically significant increase in the risk for acute leukemia (SIR = 4.5; 95 % CI 1.2 -- 12). With 10 years induction -- latency period in the calculations the elevated risk was smaller, and not significant. Based on small numbers there were also statistically significant overrisks for cancer in the peritoneum, the lip and the pleura. Conclusions A significant increase in the risk for urothelial tumors was found among the pharmaceutical workers. All but one of those with urothelial tumors were smokers, but confounding from smoking could probably not explain the risk increase.
Keywords: acute leukemia; cancer of the lip; cancer of the peritoneum; cohort; epidemiology; renal pelvis; urinary bladder; urothelial cancer